Perbedaan Persepsi Penyelenggara Nagari Luhak dan Rantau terhadap Model Pemerintahan Nagari yang Partisipatif - Yunus, Yasril - (Fakultas Ilmu Sosial Universitas Negeri Padang, 2013)
The Systems of Nagari Government in Minangkabau West Sumatra still exist both before the arrival of Dutch colonial and after independence of Indonesia in accordance with the development of the Indonesian government system. So also this time, after a change of a very basic government system. This study aimed to determine the differences in the perception of â€œluhakâ€ and â€œrantauâ€ nagari government administrators toward participatory governance model. The method used to determine this difference is a combination of descriptive statistical analysis and interactive models of analysis. The results of this study indicate that there is only a little difference in the perception between the two Nagari administrators toward the participatory governance model. In other words, the difference between the two is not so obvious. Kata Kunci: Persepsi, Nagari, Model Pemerintahan Nagari